The Sandman. Vol. 4, Season of mists - Gaiman, Neil (Gaiman, Neil. Sandman library, 1992)
Ten thousand years ago, Lord Morpheus condemned a woman who loved him to hell. When The Endless convince him this was an injustice, he travels to Hell to rescue his banished love. Lucifer, however, has other plans.